The Roles and Contributions of Stakeholders in Villages Tourism Brand Management in Bali and India - Karta, Ni Luh Putu Agustini; Kusumawijaya, Ida Ketut; Babu Kappola, Victor (Jurnal Kajian Bali (Journal of Bali Studies); Vol 10 No 1 (2020): BALI DIASPORADO - 10.24843/JKB.2020.v10.i01.p04, 2020)
The purpose of this study is to analyze the stakeholder’s roles and contributions in brand management of village tourisms in Bali and India. A descriptive qualitative research conducted in village tourisms in Bali, Indonesia with village tourisms in Andra Pradesh, India. In-depth interviews and discussions were conducted with twenty key informants involved in the management of the respective village tourisms. The findings are the stakeholders play an essential role in branding village tourisms to be able to build a good image of the destination. All activities offered in village tourisms indirectly become the brand of the village. This brand is expected to increase tourist visits, strengthen the image and keep the village tourisms sustainable.  The brand of village tourisms is an important thing to be considered by visitors in selecting the destination, so every stakeholder must contribute to create good brand image. Keywords : roles, stakeholder, branding, village tourisms, image